Pengaruh Usia terhadap Kesiapan Menikah pada Wanita Remaja - Hayati, Sri Ayatina; Prasetia, Muhammad Eka (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2023)
In contemporary society, it is common to observe the trend of early marriage. Various factors, including age, play a significant role in determining one's readiness for marriage. As an individual's age increases, it tends to have a positive impact on their preparedness for marriage and the stability of their marital relationships. This research aims to assess the extent of age's influence on marriage preparedness in young women attending Madrasah Aliyah. The study encompassed a population of 83 female adolescents enrolled in Madrasah Aliyah. Given the limited population size (less than 100), a sampling technique was employed to select the sample. The analysis method employed was simple linear regression, with age serving as the independent variable and marriage readiness as the dependent variable.. The influence of the age variable on readiness to marry adolescent women in Madrasyah Aliyah can be seen from the results of simple linear regression analysis with sig. is 0.038 < 0.05. The results of the research show that age has a significant effect on the readiness to marry among young women at Madrasah Aliyah. The research suggestion is that future researchers further expand the research population so that the research results can be used and generalized. Keywords:Readiness for Marriage; Young lady